Actividad oscilatoria en banda gamma, un promisorio nuevo marcador electroencefalográfico de dolor con potencial utilidad en la monitorización intraoperatoria - Rojas-Libano, Daniel; Rivera L., Gonzalo; Egaña T., José Ignacio (Revista Hospital Clínico Universidad de Chile, 2015)
Chronic pain is a highly prevalent condition in modern medicine. Is the main cause of consultation, the principal cause of disability worldwide and represent enormous costs for all health systems. In most cases, chronic pain is a consequence of long exposures to untreated or subtreated acute pain. Efforts should be done in situation where acute pain is expected in order to prevent its transformation into chronic pain. Surgery is one of those situations. Electroencephalography (EEG) is a powerful tool that has proved its utility for monitoring the brain under general anesthesia. Unfortunately most of the achievements have been developed in the study of unconsciousness and amnesia with little progress in the pain/nociception field. Today the electroencephalographic feature more commonly associated with pain perception is the variation in the amplitude of evoked-related potentials (ERPs). However, new date shows that the ERPs do not always reflect the stimulus intensity nor the amount of perceived pain. New data has shown strong and clear evidence that transient Gamma (30-100 Hz) oscillations are a constant electroencephalographic feature associated with pain perception. Gamma oscillations appear, then, as a promising EEG marker than has the potential to be used for monitoring pain/nociception in anesthesia.